PELATIHAN PEMAHAMAM MODERASI ISLAM MELALUI LITERASI MEDIA SOSIAL UNTUK MENANGKAL NARASI EKSTRIMISME - Suherman; Nafik Muthohhirin (TAAWUN, 2021)
Almost every student at SMA Muhammadiyah Taman Sidoarjo has a cellphone connected to a social media application, while extremist narratives based on religion often appear on social media. Not infrequently they are conditioned or provoked by these various narratives so that conservatism is rampant in their bodies. This activity aims to create and increase knowledge and understanding as well as awareness of endangering extremism for the younger generation or students. The method used is in the form of seminars and online training. The results of this activity are in the form of increased knowledge and understanding of students about the value of moderation such as love of peace, tolerance, deliberation and recitation of the al-Qur’an, hadiths, stories of friends and tabi’in.